(untitled) (American Journal of Technology and Applied Sciences, 2023)
In this article, the data obtained on the effect of plant adverse stress factors on the transpiration rate and cell sap concentration of cotton cultivars of high temperatures are presented. In addition, the current theoretical and scientific problems of studying and revealing the negative effects of high air temperature on plants, as well as the information conducted on the study of scientific and research work in this field are presented.